Kelvin-Helmholtz instability in solar spicules - H Ebadi (Iranian Journal of Physics Research, 2016)
Magneto hydrodynamic waves, propagating along spicules, may become unstable and the expected instability is of Kelvin-Helmholtz type. Such instability can trigger the onset of wave turbulence leading to an effective plasma heating and particle acceleration. In present study, two-dimensional magneto hydrodynamic simulations performed on a Cartesian grid is presented in spicules with different densities, moving at various speeds depending on their environment. Simulations being applied in this study show the onset of Kelvin-Helmholtz type instability and transition to turbulent flow in spicules. Development of Kelvin-Helmholtz instability leads to momentum and energy transport, dissipation, and mixing of fluids. When magnetic fields are involved, field amplification is also possible to take place